REKONTRUKSI REMAJA PECANDU ZAT ADIKTIF MELALUI PENANAMAN NILAI-NILAI SPIRITUAL OLEH KOMUNITAS COPLER - Ahmad Syamsul Muarif (UNIVERSITAS BENGKULU, 2019)
The problem discussed in this study is how the form of planting spiritual values carried out by the copler community in adolescents who habitually spree to addicted addicts. The purpose of this study is to find out how to instill spiritual values so that they are easily accepted by adolescents who have the habit of spree and addicted addicts, from negative things to very positive things. The method used in this study is a qualitative method of phenomenology. Data obtained from interviews, observations, and documentation. The results of research conducted at Ukhsafi Copler Comunity DIY, they carry out spiritual value planting which aims to reconstruct themselves by means of coffee together, drinking together, singing together, participation in the remembrance majors, from copler activities in approaching to instilling the value of religious religiosity through the meaning of the sacred song in the dust, so that some values can be embedded in adolescents namely; the value of faith, moral values, istiqamah values and ukhwah values.